STUDI KELAYAKAN PROYEK PERKEBUNAN KELAPA SAWIT PT. HENRISON INTI PERSADA, PAPUA - I WAYAN BUDIASA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2002)
The Nucleus Estate and small-holder Development Project (NES-Project) of Elaeismelanococca which is developed in Papua Province (Irian Jaya) is inspired by Henrison IntiPersada Enterprise. It has involved about 5,650 families and covered 19,333 hectares. TheNES-Project requires an investment of Rp 231.79 billions.Feasibility study of this project is overlooked from its marketing, technical,operational management, economic and financial aspect. Data analysis includes descriptiveand quantitative analysis.The result of study shows that The NES-Project of Elaeis melanococca would becompetitive investment according to the investment criteria of Net Present Value (NPV) andInternal Rate of Return (IRR). The project suitability depends on prospective marketing, theavailable technology, operational management ability, and which can give benefiteconomically. Financial ratio analysis shows that this project is profitable, liquid, solvent,and efficient, but from the sensitivity analysis, this project seems to be sensitive (especially inThe Nucleus Estate), if viewed from the IRR value which only slightly bigger compared tothe social discount rate, which expected.